Determinants of child schooling in Kwara State, North Central Nigeria - Adebayo Mohammed Ojuolape; Saidatulakmal Mohd (Cogent Social Sciences, 2024)
Nigeria has one of the largest out-of-school populations in the world and the largest in Africa. This study analyses the determinants of socioeconomic issue of out-of-school children. This issue is a key component of the UNSDG4. Multinomial logistic regression was used to analyse child schooling enrolment. 1120 questionnaires were administered to household heads across Kwara State, Nigeria. This study highlights the importance of access and cost in improving child schooling and how parents with low educational attainment tend to pay less attention to their child’s schooling. The study recommends the increased provision of schools within or near rural communities, tuition-free education, and sensitizing parents with low levels of education on the importance of education in their child’s development.